The Influences of Symbiotic Host Gut Microbiota During Obesity and Diabetes - Harmit S Ranhotra (Iranian Journal of Diabetes and Obesity)
The resident gut microbiota is a complex and dynamic entity and at times their imbalance (dysbiosis) can trigger the onset of diseases. Dysbiosis are known to be correlated to host metabolic disease, liver disease, immune complications amongst few others. Dysbiosis can deregulate the biosynthesis and secretion of metabolites by the microbiota which is normally considered beneficial to the host. Altered metabolites availability can modulate host organs/tissues functions which may influence certain disease onset and progression. Obesity and diabetes are diseases that exhibits a correlation with significant change in gut microbiota composition and diversity. Modulation in the secretion of gut microbiota-derived metabolites during dysbiosis appears to influence the onset and progression of obesity and diabetes. However, direct physiological link between the gut microbiota and obesity and diabetes is not confirmed yet and remains a challenge for further investigations. In this article, findings where by perturbation of the gut microbiota may contribute towards obesity and diabetes in the host are reviewed.